الرقابة الداخلية على إيرادات ومصاريف الدراسة المسائية في جامعة الموصل الواقع وآفاق التطوير - بلال امجد محمد الصائغ; طه احمد حسن ارديني; ياسمين اكرم جاسم (PROSPECTIVE RESEARCHES, 2023)
The purpose of the research is to clarify the specificity of the activities of the educational institutions and their impact on the elements of the internal control system and the evaluation of the internal control system at the University of Mosul - evening studies as well as proposing some aspects to develop the internal control system at Mosul University. The research was divided into three axes, While the second axis was devoted to give a theoretical lecture on internal control of revenues and expenses in universities - evening studies, Finally, the third axis was devoted to evaluating the system of internal control of revenues and expenses at the University of Mosul - evening studies and proposing some developmental aspects to address the disadvantages of the current system and focus on the strengths of it. The researchers propose to introduce the analytical procedures within the work of the internal control system at the University of Mosul - evening studies. Finally, the degree of compatibility of the internal control system with the objectives of the educational institution should be evaluated.